FEATURES OF PERSONNEL MANAGEMENT SERVICE AS SUBJECT OF PERSONNEL POLICY - Kyrii S. (Theory and Practice of Public Administration, 2019)
The socio-management relations in democratic states are characterized by humanist orientation and a prevailing anthropocentric approach to managing social affairs. In the situation of external threat and internal challenges, the problem of providing public authorities with the personnel that could comply with the current management requirements is highly emphasized. The state personnel policy is to take the lead in this matter. Formation and implementation of the state personnel policy as a key task of a modem democratic law-governed state with a social focus are widely debated in the scientific circles and among practitioners. The existing papers research the specific features of the mechanisms and ways to implement state personnel policy, however, without stating the differences between the tasks and functions of different policy subjects. The paper objective is to identify the essential features, characteristics, tasks and functions of the personnel management service of public authorities, taking into account the global trends of public administration humanization. The notion of ‘staffing service’ in the Ukrainian scientific discourse is closely connected with such scientific categories as ‘staff’, ‘staffing policy’, ‘staffing processes’ and ‘staffing technologies’. To a large extent, this is associated with public authorities as distinct from ‘personnel management services’ which, alongside with public authorities, have relevance to managing personnel of NGOs and private sector organizations, relating to such notions as ‘personnel’ and ‘personnel management’. By the nature of the tasks and methods of organizational impact, all the functions concerning implementation of the personnel policy in a public authority can be divided into three main groups: administrative, social, and psychological. The administrative, social, and psychological functions are typical of the activity of both staffing service and personnel management service. However, while the staffing service is focused on realization of the administrative function, the personnel management service activity is shifted towards the social and psychological functions, which complies with the general global trends of social relations humanization in democratic countries. The differences between the staffing service and personnel management service lie in the following: – approaches to interpreting the notions of ‘staff’ and ‘personnel’, ‘staffing service’ and ‘personnel management service’; – objects of the personnel policies of personnel management service and staffing service; – the emphasis laid on the administrative functions of the staffing services of public authorities and the focus on the social and psychological functions of personnel management services. The subsequent global trends of humanization of the public administration sphere have led to some organizations’ transforming their staff management systems into the systems of human resource management and human capacity management, which calls for further scientific research of their functional and organizational capabilities, key goals, tasks and lines of action, as well as elaboration of the methodology for their functioning with account of the innovation management component.